The Conceptism of ‘Talent’ as a Growth Factor in the Verses of the Holy Quran from the Perspective of Allameh Tabataba'i and Sadr al-Muta'allihin - Jamileh Alam-ol-Hoda; Atekeh Qasem Zadeh; Hajar Mohajer Darabi (آموزه‌های قرآنی)
The important thing about a human being and his or her movement in the path of education is that what is considered in relation to him or her must be in accordance with the Truth of Being and taking into account all his dimensions in order to draw the right path to its true end. One of the existential dimensions of man is his talent. Therefore, in this research, we seek a thorough and accurate explanation of the concept of “talent” as one of the basic concepts of education. This explanation is based on the verses of the Holy Qur'an, the interpretation of al-Mizan, the interpretation of Sadra, and the reliance on the principles and fundamentals of transcendent wisdom, in particular the reality of existence, the quintessential movement and the doubt unity. The research method is conceptual analysis and qualitative content analysis. According to the findings of the study, human talents are not separate from one another and are not inherently distinct but they are in fact a gradual truth that with each emergence of this fact provides the ground for the emergence of some other and the field of the emergence of others disappears. Hence, talent is seen as a cause of growth in one sense and a caused of growth in another. Once every talent is inherent and the next it is acquired and imparted. Talents are given to human beings according to their needs and abilities, and in the end it is the perfection of good talents that is the perfection of human development.